The tell tail heart - Conte, Cate (Conte, Cate. Cat café mystery., 2019)
Maddie is hoping to have some downtime during Daybreak Island<U+2019>s off-season to tackle her to-do list. Her grandfather<U+2019>s house-turned-cat-café is under construction and she<U+2019>s also scoping out places to open a juice bar on the island. On top of that, her relationship with adorable dog groomer Lucas has taken a pawsitive turn. But easy is getting harder every day for Maddie, especially when a big-name writer who<U+2019>s on the island working on a new project winds up floating in the canal. This, on the exact same day an eccentric woman shows up at the cafe claiming Maddie<U+2019>s cat, JJ, is hers. As the investigation into the dead writer picks up, Maddie realizes that even the neighbors she<U+2019>s known all her life might be keeping secrets that go deep into the heart of this small seaside town. Meanwhile, a killer remains at-large...and on the prowl.